(3GdeGFIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s ((3HZOGO eOjfI GdSdGe s)
(3ChdgG (B:s
(3gPG gh GdcJGH GdChd ef cJHfG ai UfGYI GdWH hbUOfG ajg Cf fJcde ajeG jLH JbOjeI bHd GdTQh Y ai Yde GdWH s
(3BNQgG (B:s
(3hgG gfG adfbWY GdcdGe ai gPG GdcJGH abO HdZ GdJeGe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs